Can we really reduce ethnic prejudice outside the lab? A meta-analysis of direct and indirect contact interventions - Lemmer, Gunnar; Wagner, Ulrich (European journal of social psychology, 2015)
The present meta‐analysis tested the effectiveness of contact‐based interventions for the reduction of ethnic prejudice. Up to now, a meta‐analysis summarizing the results of real‐world interventions that rest on the intergroup contact theory has been missing. We included evaluations of programs realizing direct (i.e., face‐to‐face) and/or indirect (i.e., extended or virtual) contact in real‐world settings outside the lab. The interventions' effectiveness was tested shortly after their end (k = 123 comparisons, N = 11 371 participants) and with a delay of at least 1 month (k = 25, N = 1650). Our data show that contact interventions improve ethnic attitudes. Importantly, changes persist over time. Furthermore, not only direct but also indirect contact interventions are successful. In addition, contact programs are effective even in the context of a serious societal conflict (e.g., in the Middle East). Although changes are typically larger for ethnic majorities, there is an impact on minorities, too. Finally, contact interventions not only improve attitudes toward individuals involved in the program, their effects also generalize to outgroups as a whole. In sum, social psychology provides an intervention for prejudice reduction that can be successfully implemented in the practical field. Copyright © 2015 John Wiley & Sons, Ltd.